THE UNIFORM RECOGNITION ITEMS IN THE FINANCIAL STATEMENTS - Gadau, Liana (Annals of Spiru Haret University. Economic Series, 2016)
Through the issues presented and analyzed, we want to highlight the overwhelming importance of the recognition process of the elements in the financial statements, resulted in the recognition criteria, more or less detailed, depending on the chosen normalization framework, but which helps to the accurate positioning of items in the financial statements and thus the credibility and relevance of the information contained therein. The necessity of normalization process of recognition of the elements in the financial statements appeared at different levels of the accounting referential, and here we refer particularly at the two basic referential: the international and the American one, which will constitute the basis of our analysis on this paper. The result of the normalization process of recognition of the items from the financial statements has result in the establishment of the criteria for recognition, which contribute to proper positioning of elements in the financial statements, thus giving credibility and relevance of the information contained therein.